2018
DOI: 10.31674/mjn.2018.v10i01.008
|View full text |Cite
|
Sign up to set email alerts
|

The Context of Postnatal Depression in Malaysia: An Overview

Abstract: Sociocultural contexts of motherhood have been found to have a link with postnatal depression. Malaysia has a wide-range of cultural and ethnic backgrounds that offers a wonderful chance to understand the different role of cultures and postnatal practices in relation to postnatal depression. The purpose of this paper is to discuss the link between the Malaysian healthcare system, social and cultural context, the existing health policy and postnatal depression. This paper highlights that while there are differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Existing literature suggested that there is less emphasis on the emotional aspects in the process of disease recognition and understanding PND within Malaysian primary healthcare setting [ 24 ]. There is also less attention to primary prevention such as training of HCPs working within MCH clinics that could enable them to screen for PND, to deal with cases, and to provide public education, awareness programmes and screening activities [ 24 ].Without such specific training, antenatal or postnatal women with any mental health issues (including PND) are commonly referred from MCH clinic to the psychiatric unit in the hospital. When it is required, they are then treated within the same psychiatric setting as patients with general depression and other psychiatric problems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing literature suggested that there is less emphasis on the emotional aspects in the process of disease recognition and understanding PND within Malaysian primary healthcare setting [ 24 ]. There is also less attention to primary prevention such as training of HCPs working within MCH clinics that could enable them to screen for PND, to deal with cases, and to provide public education, awareness programmes and screening activities [ 24 ].Without such specific training, antenatal or postnatal women with any mental health issues (including PND) are commonly referred from MCH clinic to the psychiatric unit in the hospital. When it is required, they are then treated within the same psychiatric setting as patients with general depression and other psychiatric problems.…”
Section: Resultsmentioning
confidence: 99%
“…For example, antenatal and postnatal women are not routinely screened for depression within the MCH clinics, although the international guidelines for diagnosing mental disorders (i.e. DSM-5) have been widely used within the psychiatric settings in Malaysia [ 36 ]. Without a specific policy on screening and care for maternal mental health disorders, antenatal or postnatal women with any mental health disorders (including PND) may be overlooked and probably underdiagnosed within MCH clinics in Malaysia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In current practice, the nurse-midwife (referred to as 'bidan') plays an important role in the community by identifying signs and symptoms of mental illness in antenatal and postnatal mothers. 10 help them develop a broader understanding of perinatal mental disorders. This training enhances early detection of such disorders and provides basic mental healthcare and treatment for a range of mental health problems in MCH clinics.…”
Section: Mental Healthcare Services In the Perinatal Periodmentioning
confidence: 99%
“…In Malaysia, healthcare services for individuals of childbearing age are delivered by maternal and child health (MCH) clinics. 10 In rural areas, these healthcare services are managed by community clinics that also provide healthcare for newborns. 10 These clinics are staffed by family medicine specialists, obstetricians, medical officers, nurse-midwives, physiotherapists, occupational therapists, nurses, assistant medical officers, nutritionists and dietitians.…”
Section: Healthcare Services For Individuals Of Childbearing Agementioning
confidence: 99%